THE EFFECT OF ACUPRESSURE ON DYSMENORRHEA AMONG ADOLESCENTS IN THE WORKING AREA OF PUSKESMAS MUNJUL JAYA, WEST JAVA - Purwasari, Eka; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2025)
Background: Primary dysmenorrhea is a common menstrual disorder among adolescent girls that can disrupt daily activities and reduce quality of life. One non-pharmacological method to relieve pain is acupressure, which involves applying pressure to specific points on the body to stimulate blood circulation and release endorphins. However, studies on its effectiveness in the working area of Puskesmas Munjul Jaya remain limited. Purpose: To determine the effect of acupressure on the level of dysmenorrhea pain among adolescent girls in the working area of Puskesmas Munjul Jaya. Methods: This quasi-experimental study employed a pretest-posttest one group design. The sample consisted of 36 adolescent girls with primary dysmenorrhea, selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after acupressure intervention, which was performed for three consecutive days. Data were analyzed using the paired samples t-test. Results: The mean pain score before the intervention was 7.11, which decreased to 3.17 after the intervention, with a statistically significant difference (p < 0.001). Conclusion: Acupressure is effective in reducing dysmenorrhea pain among adolescent girls and can be recommended as a safe and simple alternative therapy.